How does accreditation influence staff perceptions of quality in residential aged care?. (12th June 2017) - Hogden, Anne; Greenfield, David; Brandon, Mark; Debono, Deborah; Mumford, Virginia; Westbrook, Johanna; Braithwaite, Jeffrey
Abstract : Purpose: Quality of care in the residential aged sector has changed over the past decade. The purpose of this paper is to examine these changes from the perspectives of staff to identify factors influencing quality of residential aged care, and the role and influence of an aged care accreditation programme. Design/methodology/approach: Focus groups were held with 66 aged care staff from 11 Australian aged care facilities. Data from semi-structured interviews were analysed to capture categories representing participant views. Findings: Participants reported two factors stimulating change: developments in the aged care regulatory and policy framework, and rising consumer expectations. Four corresponding effects on service quality were identified: increasing complexity of resident care, renewed built environments of aged care facilities, growing focus on resident-centred care and the influence of accreditation on resident quality of life. The accreditation programme was viewed as maintaining minimum standards of quality throughout regulatory and social change, yet was considered to lack capacity of itself to explicitly promote or improve resident quality of life. Research limitations/implications: For an increasingly complex aged care population, regulatory and societal change has led to a shift in service provision from institutional care models to one that is becoming more responsive to consumer expectations. The capacity of long-established and relatively static accreditation standards to better accommodate changing consumer needs comes into question. Originality/value: This is the first study to examine the relationship between accreditation and residential aged care service quality from the perspectives of staff, and offers a nuanced view of "quality" in this setting.